Analyzing the Influence of Imaging Resolution on Polarization Properties of Scattering Media Obtained From Mueller Matrix - Shao, Conghui; Chen, Binguo; He, Honghui; He, Chao; Shen, Yuanxing; Zhai, Haoyu; Ma, Hui (Frontiers in Chemistry, 2022)
Mueller matrix contains abundant micro- and even nano-structural information of media. Especially, it can be used as a powerful tool to characterize anisotropic structures quantitatively, such as particle size, density and orientation information of fibers in the sample. Compared with unpolarized microscopic imaging techniques, Mueller matrix microscopy can also obtain some essential structural information of the sample from the derived parameters images at low resolution. Here to analyze the comprehensive effects of imaging resolution on polarization properties obtained from Mueller matrix, we firstly measure the microscopic Mueller matrices of unstained rat dorsal skin tissue slices rich in collagen fibers using a series of magnifications or numerical aperture (NA) values of objectives. Then the first-order moments and image texture parameters are quantified and analyzed in conjunction with the polarization parameters images. The results show that the Mueller matrix polar decomposition parameters diattenuation D, linear retardance δ and depolarization Δ images obtained using low NA objective retain most of the structural information of the sample, and can provide fast imaging speed. In addition, the scattering phase function analysis and Monte Carlo simulation based on the cylindrical scatterers reveal that, the diattenuation parameter D images with different imaging resolutions are expected to be used to distinguish among the fibrous scatterers in medium with different particle sizes. This study provides a criterion to decide which structural information can be accurately and rapidly obtained using transmission Mueller matrix microscope with low NA objectives to assist pathological diagnose and other applications.